Optimizing the process of fire detection in warehouses considering the type and location of fire detectors - Sharyy, Volodymyr; Pasnak, Ivan; Renkas, Artur (Eastern-European Journal of Enterprise Technologies, 2022)
An integral condition for avoiding damage due to fires in warehouses, or at least minimizing them, is the early detection of fires using fire protection systems, as well as its timely localization. Depending on which fire detectors are selected to protect the relevant premises and where they are installed, the time of operation of all elements of automatic control systems in case of a fire will depend. The review of literary data revealed that at present there is no comprehensive approach to choosing the optimal placement in warehouses. In addition, the optimal placement of fire detectors within the room, taking into consideration the type of fire load, has not been sufficiently studied. Therefore, the purpose of the current study is to establish the dependence of the time of operation of different types of fire detectors on the type of combustible material, namely its mass burnout rate, distance, and height of placement of detectors from a potential fire site. This paper reports a procedure for conducting an experimental study to identify the appropriate dependence for warehouses. The results of the experiments showed that the most effective in warehouses are targeted fire smoke detectors and aspiration systems. Based on the results of a complete factor experiment, nonlinear empirical dependences to determine the time of operation of smoke fire detectors on the above factors were built. The resulting empirical dependences make it possible to choose fire detectors and optimally place them within a room. The average error in these dependences when compared with the experimental data is 6.9 %. The use of the derived dependences makes it possible to reduce the time of operation of fire detectors by 14 s in comparison with their placement in accordance with building codes